Nurse burnout before and during the COVID-19 pandemic: a systematic comparative review - Rizzo, Amelia; Yıldırım, Murat; Öztekin, Gülçin Güler; Carlo, Alessandro De; Nucera, Gabriella; Szarpak, Łukasz; Zaffina, Salvatore; Chirico, Francesco (Frontiers in Public Health, 2023)
This review aimed to compare available evidence examining burnout using the Maslach Burnout Inventory (MBI) in nurses before and during the COVID-19 pandemic. The specific objective was to compare nurse burnout scores in terms of emotional exhaustion, depersonalization, and personal accomplishment. A comprehensive search was conducted for studies on nurses' burnout using the MBI published between 1994 and 2022. Nineteen studies conducted prior to the pandemic and sixteen studies conducted during the pandemic were included and compared using the criteria from the Joanna Briggs Institute Critical Appraisal Tool. Surprisingly, the results indicated that nurses' burnout scores did not differ significantly before (N=59,111) and during (N=18,629) the pandemic. The difference observed was qualitative rather than quantitative. The outbreak of the COVID-19 pandemic exacerbated an already critical situation, and while COVID-19 may serve as an additional triggering factor for staff mental illness, it cannot solely explain the observed burnout levels. These findings underscore the need for long-term clinical and preventive psychological interventions, suggesting that psychological resources should not be limited to emergencies but extended to address the ongoing challenges faced by nurses.